Influence of the projection plane and the markers choice on the X-factor computation of the golf swing X-factor: a case study - Bourgain, M.; Sauret, C.; Marsan, T.; Perez, M. J.; Rouillon, O.; Thoreux, P.; Rouch, P. (Computer Methods in Biomechanics and Biomedical Engineering, 2020)
X-factor seeks to account for the dissociation between the shoulder and the pelvis girdles. It has been believed to be a key parameter for golf swing performance. However, several computational methods have been used and there is currently no consensus. Even if some comparison studies were performed, they remain incomplete.